Cervical Cancer during Pregnancy at Siriraj Hospital: A Thirteen-Year Review (1998-2010) - Chairat Leelaphattanadit; Saifon Chawanpaiboon; Siripong Sawasdimongkol (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To determine the prevalence of cervical cancer, staging, presenting symptoms, gestational age at diagnoses, screening and diagnostic methods, and pregnancy outcomes of pregnant women at Siriraj Hospital. Materials and Methods: Medical records of pregnant women diagnosed with cervical cancer at Siriraj Hospital from 1998 to 2010 were reviewed. Results: Twelve cases of pregnant women with cervical cancer were identified during this study period of 13 years. Eight of them were diagnosed with stage I and 4 of them were in stage II according to pathological diagnosis. All patients presented with the symptom of abnormal bleeding per vagina. Four patients with stage II disease were diagnosed early in pregnancy and chose to terminate pregnancy. Five patients with stage I disease delivered by cesarean section, radical hysterectomy with pelvic node dissection (RHND) was performed following pregnancy termination in 2 cases whose future fertility is not desired. Conclusion: The prevalence of cervical cancer during pregnancy at Siriraj Hospital was low. Cervical cancer screening in all women should be considered in the program before planning a conception.